Under-reported finding in acral erythema multiforme - Adriana G Pena Romero; Judith Dominguez Cherit; Amanda C Guzman Abrego (Wolters Kluwer Medknow Publications, 2015)
Erythema multiforme is an acute muco-cutaneous hypersensitivity reaction with a variety of etiologies. It is characterized by a skin eruption, with or without oral or other mucous membrane lesions. General characteristics and treatmet have been described , but nail findings are rarely reported  Here we present a 26-year-old patient with acral erythema multiforme and erythronychia adjacent to skin lesions on the back of the hands. To our knowledge this association had not been reported before.